KEARIFAN LOKAL BERBASIS ISLAM DALAM PELESTARIAN LINGKUNGAN HIDUP - Sulaiman Alqomayi (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
The disasters that are related to heavy rain such as flood, landslideand dry climate especially in Central Java are problems which need solutions.This article tries to explore the myth to preserve water resource asa local wisdom in Sempor society in Kebumen regency. This article usesHomo Ecologus and Cultural Identity approach to understand the object.Based on that opinion, it is found that the myth is rooted in the value andpoint of view of Sunan Buyut Saringan who always emphasized on thankfulnessof everything that has been given by God.